Canonical Correlation Analysis for Understanding Foundational-Advanced Chemistry Classes Relationship and Their Role in Preparing Preservice Teacher - Almubarak, Almubarak; Prayogi, Restu; Yasim, Sukmawati; Adhani, Aidil (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Mental models and the strength of basic chemistry concepts are the primary foundation for students to avoid obstacles in highly complex material. On the other hand, students' understanding of basic chemistry concepts has not been optimally developed, even though this situation impacts understanding complex material at the advanced level. However, simultaneous analysis of the relationship between foundational and advanced level courses using a statistical test approach is rarely done, even though this condition impacts learning success at the upper level. The purpose was to determine (1) the simultaneous relationship between prerequisite and advanced level courses, and (2) the contribution of each prerequisite course in predicting student academic achievement in advanced level classes. This study used a quantitative correlational design with canonical correlation analysis, involving introductory chemistry and school chemistry courses as prerequisites and basic organic chemistry and physical organic chemistry as advanced-level variables. Data collection used documentation techniques for students' cognitive learning outcomes in the chemistry education study program. The study results showed that the first canonical function (function 1) obtained a correlation of 0.99398 with p = 0.000 and an eigenvalue of 82.31551. This indicates a significant simultaneous relationship, with introductory chemistry contributing the most, while school chemistry contributed little. This study emphasises the importance of strengthening mastery of basic chemistry concepts and integrating pedagogical content to support student academic success and preparedness. This study provides a fundamental foundation for the importance of developing chemistry education programs that impact student academic performance while preparing them to face increasingly inclusive and connected global challenges through modern learning.